2008
DOI: 10.1080/10601320802222616
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a New Dioxime and Its Heterotrinuclear BF2+Capped Complexes

Abstract: v-Isonitrosoacetophenone (1), phenylglyoxime (2), chlorophenylglyoxime (1), dopaminophenylglyoxime (3) and [(salen/saloph)Fe] 2 O (4) have been synthesized as described in the literature procedure. [Fe(III)(salen/saloph)dopaminophenylglyoxime)] (starting complexes) have been synthesized from dopaminophenylglyoxime and tetradentate schiff bases which contain dinuclear Fe(III) oxygen-bridges N,N 0 -bis(salicylidene)ethylenediamine (salenH 2 ) and bis(salicylidene)-o-phenylenediamine (salophH 2 ). The new heterot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Obtained tripodal oxySchiff bases were characterized by their elemental analyses, thermal analyses, 1 H NMR, and FT-IR, AAS and mass spectral data. [34][35][36][37][38][39]. These complexes are the examples of tripodal multinuclear complexes bridged by carboxylate anions to the iron and chromium centers (Scheme 2).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Obtained tripodal oxySchiff bases were characterized by their elemental analyses, thermal analyses, 1 H NMR, and FT-IR, AAS and mass spectral data. [34][35][36][37][38][39]. These complexes are the examples of tripodal multinuclear complexes bridged by carboxylate anions to the iron and chromium centers (Scheme 2).…”
Section: Resultsmentioning
confidence: 98%
“…The vibrations of the azomethine C N, triazine C N and C-O-C of the free ligands were observed at 1618-1605, 1574-1560 and 1375-1359 cm −1 range, respectively [34][35][36][37][38]42,43]. In the complexes, the fact that these bands were shifted to lower frequencies has indicated that oxygen atoms of the dendrimeric oxy-Schiff base ligands are coordinated with the ligand complexes.…”
Section: Ft-ir Spectra Interpretations Of the Ligands And Complexesmentioning
confidence: 90%
See 3 more Smart Citations